Formylpeptide receptor 1 mediates the tumorigenicity of human hepatocellular carcinoma cells. (1st February 2016) - Zhang, Liang; Wang, Huanyu; Yang, Tianshu; Su, Zhifeng; Fang, Dan; Wang, Yafeng; Fang, Jiazhu; Hou, Xinwei; Le, Yingying; Chen, Keqiang; Wang, Ji Ming; Su, Shao Bo; et al.
Abstract: G protein-coupled chemoattractant receptors (GPCRs) have been implicated in cancer progression. Formylpeptide receptor 1 (FPR1) was originally identified as a GPCR mediating anti-microbial host defense. However, the role of FPR1 in tumorigenesis remains poorly understood. The current study aims to investigate the potential of FPR1 to regulate human hepatoma growth and invasion. We found the FPR1 gene and protein expression in human intratumoral and peritumoral tissues of hepatocellular carcinoma (HCC) specimens and in human hepatoma cell lines. FPR1 activation mediated the migration, calcium mobilization and ERK-dependent IL-8 production by hepatic cancer cells. FPR1 knockdown substantially reduced the tumorigenicity of hepatoma cells in nude mice. Necrotic hepatic tumor cells released factor(s) that activated FPR1 in live tumor cells. Our results indicate a critical role of FPR1 in the progression of malignant human hepatic cancer. FPR1 thus may represent a molecular target for the development of novel anti-hepatoma therapeutics.